History of archaeology : international perspectives : proceedings of the XVII UISPP World Congress (1-7 September, Burgos, Spain). - Delley, Géraldine, (Archaeopress archaeology., 2016)
The present volume gathers the communications of the three sessions organized under the auspices of the Commission 'History of Archaeology' at the XVII UISPP World Congress Burgos 2014.